REFLEKSI PLURALISME MELALUI FILM ANIMASI SI ENTONG SEBAGAI IDENTITAS BUDAYA INDONESIA - Meta Sya; Rustono Farady Marta; Ido Prijana Hadi (Jurnal Riset Komunikasi (JURKOM), 2020)
Indonesia is known as a country full of diversity, and it is united through the motto of the Indonesian people, namely “Bhinneka Tunggal Ika”. However, this motto must be maintained by introducing it to children from an early age. The use of technology can be utilized to introduce the motto through children's film animation. One of the Indonesian works who reflects the spirit of pluralism and displays cultural identity, namely Si Entong. The uniqueness shown in the Entong movie is the character of children who come from various ethnic groups and the use of dialect. Relying on the theory of identity negotiation was proposed by Stella Ting-Toomey, the authors' findings in the animated film "Si Entong" were elaborated with Phillip Mayring's qualitative content analysis method. This research rests on an interpretive paradigm to find three main elements of content analysis, including: abstraction, application and structuration. These three stages are identified by the researcher as a reflection of pluralism and cultural identity in the story of " Si Entong".